PENERAPAN KOOPERATIF ROUND CLUB UNTUK MENINGKATKAN HASIL BELAJAR TENTANG SIKAP TANGGUNGJAWAB DALAM BERINTERAKSI DENGAN ORANG LAIN PADA PESERTA DIDIK KELAS V SDN LAMATOU TAHUN AJARAN 2020-2021 - Maria Ema Koten (Jurnal Pelayanan Pastoral, 2022)
Responsibility is an attitude that is accountable to God, oneself and others. Humans are aware of themselves living together with other people, jointly providing meaning and value and humanizing each other. Humans become individuals precisely in the recognition of others. This research is included in classroom action research. Round club cooperative method. The research location is Lamatou State Elementary School, Lewolema District, East Flores Regency. The subjects of the research were 16 students of class V SDN Lamatou. The research was carried out for 2 months, starting from January to February 2021. This research was carried out in two cycles. The research procedure consisted of two stages. The first stage is the stage of determining the learning model and the second stage is the application of the learning model. The first stage and the second stage have the same research object because in the first stage a search is carried out to determine the learning model that is in accordance with the real conditions faced by students. At this stage, observations were made of students, and based on the results of observations, students were interviewed. The results of the interviews were correlated with the home visit data. At the end of the first stage, students are given formative tests as a pre-cycle activity and at the second stage, namely the application of the learning model of the first stage of the search results. In this stage, students are given treatment in two cycles